Fibrin-based interpenetrating polymer network biomaterials with tunable biodegradability. (7th April 2015) - Bidault, L.; Deneufchatel, M.; Hindié, M.; Vancaeyzeele, C.; Fichet, O.; Larreta-Garde, V.
Abstract: Biodegradable interpenetrating polymer networks (IPNs) were conceived. Polyvinyl alcohol (PVA) was chosen as synthetic polymer network in which serum albumin (SA) was added to allow the material forthcoming degradation by enzymes. The PVA–SA co-networks were synthesized by free radical copolymerization of polyvinyl alcohol (PVAm) and serum albumin (SAm), both previously modified with methacrylate functions. Fibrin gel which plays a key role in wound healing and hemostasis, was selected as second partner in the IPN. Fibrin/PVA–SA IPNs were synthesized rapidly through an in situ process and they are easy to handle. The homogeneous distribution of SA and fibrin in the IPN was checked by confocal laser scanning microscopy. As expected, the copolymerization of SA with PVA allows enzyme hydrolysis of both the co-networks and the corresponding IPNs with rates depending on the total protein concentration, following the Michaelis–Menten kinetic model. IPN proteolysis is therefore easily tunable. This original approach allows for the production of IPNs enzymatically degradable. Finally, these biodegradable IPNs are good supports for cell growth because their degradability enhances viability of fibroblasts cultured on their top compared to non-biodegradable material. As they mimic the physiological microenvironment of tissues, they are promising candidates for tissue engineering. Graphical abstract: Highlights: Biodegradable materials with interpenetrating polymer network (IPN) architecture. Co-networks of methacrylate-modified polyvinyl alcohol (PVA) and serum albumin (SA). Enzymatically degradable PVA-co-BSA/fibrin interpenetrating polymer networks (IPNs). IPN's hydrolysis depends on protein content and follows the Michaelis–Menten model. Biodegradable fibrin-based IPNs as good supports for cell growth.